The effect of commercial feed versus kitchen waste on the performance of guinea fowl - Zainudin, Nurul Hidayah (2017)
A study was conducted to compare the growth performance of guinea fowl by using two treatments which is commercial feed and kitchen waste. The aim of this research is to evaluate the effect of using kitchen waste as a feed on performance of guinea fowl. The main objective is to determine the effects of different types of feed that is commercial versus kitchen waste on the growth performance of guinea fowl. This research has been done in farm 2, Universiti Putra Malaysia. A total of thirty guinea fowl used in this study and the guinea fowl were reared for 12 weeks. The Guinea fowl was divided into two groups which are fed by the commercial feed and kitchen waste. The flock behavior of the guinea fowl was monitored to ensure the keets show normal behavior. The behavior is important to observe to know the keets are comfortable or not. The parameter used in this study were weekly body weight, weekly body weight gain, weekly feed intake, and weekly feed conversion ratio. The body weight was taken each week to get results. The feed given to the keets were formulated from the kitchen waste and also the commercial feed. For the kitchen waste, the food waste has been collected from the restaurant and the unwanted substance was removed. Then, the kitchen waste was washed or cleaned with water to remove the dirt and oil. It is to make sure the quality of the kitchen waste to be given to the keets. Besides that, the kitchen waste were dried under the sun and then put into the oven to make sure it dry properly. Finally, the dried kitchen waste then was grind into smaller particles and given directly to the keets. The mean body weight and body weight gain for treatment 1 which is commercial feed shows slightly higher compared to the treatment 2 which is kitchen waste but not significantly different. For the feed intake and feed conversion ratio also showed no significant different in most week but slightly significant different in few week because the factors of adaptation period, food waste, and weather. In conclusion, the commercial feed showed a better performance result compared to the kitchen waste. But, the kitchen waste still can be used a feed source in order to cut the feed cost in poultry industry.